Evaluation of the antifungal activities of various extracts from Pistacia atlantica Desf - Mehraban Falahati; Asghar Sepahvand; Hossein Mahmoudvand; Parastoo Baharvand; Siamak Jabbarnia; Aynaz Ghojoghi; Mohammad Yarahmadi (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Despite the availability of various treatments for fungal diseases, there are some limitations in the management of these conditions due to multiple treatment-related side-effects. The present study was designed to investigate the antifungal properties of different extracts from Pistacia atlantica Desf. Materials and Methods: Different parts of P. atlantica (i.e., dried fruit, fresh fruit and dried leaf) were separately extracted via percolation method with 80% methanol and water. Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine the main constituents of leaf and fruit extracts from P. atlantica. In vitro anti-Candida activities of the extracts against Candida albicans, Candida glabrata and Saccharomyces cerevisiae were studied. For this purpose, the minimum inhibitory concentrations (MICs) and minimum fungicidal concentrations (MFCs) were determined, using broth microdilution method, according to the modified M27-A3 protocol on yeasts, proposed by the Clinical and Laboratory Standards Institute (CLSI). Results: Based on GC/MS analysis, the main constituents of P. atlantica fruit extracts were &beta-myrcene (41.4%), &alpha-pinene (32.48%) and limonene (4.66%), respectively, whereas the major constituents of P. atlantica leaf extracts were trans-caryophyllene (15.18%), &alpha-amorphene (8.1%) and neo-allo-ocimene (6.21%), respectively. As the findings indicated, all the constituents exhibited both fungistatic and fungicidal activities, with MICs ranging from 6.66 to 26.66 mg/mL and MFCs ranging from 13.3 to 37.3 mg/mL, respectively. Among the evaluated extracts, the methanolic fresh fruit extract of P. atlantica was significantly more effective than other extracts (P<0.05). Conclusion: Based on the findings of the present study, novel antifungal agents need to be developed, and use of P. atlantica should be promoted in the traditional treatment of Candida infections.